Peningkatan Mutu Pendidikan di Sekolah Dasar melalui Program Kampus Mengajar Angkatan 3 - Muyassaroh, Izzah; Masrurah, Siti Nurhaliza; Oktaviani, Rhisma Putri (CV. Creative Tugu Pena, 2022)
Improving educational quality units requires synergy from the various parties not only from the school stakeholders concerned but also the participation of universities and the government. Kampus Mengajar is one of the community services programs that aims to unite the synergy of the government, academics, and practitioners to accelerate the improvement of the quality of education after the learning loss due to the Covid-19 pandemic. This service activity was conducted in several stages like debriefing, coordination, deployment, needs analysis, program planning, implementation, reflection and evaluation, and student withdrawal. This article aims to describe the efforts to assist in improving the quality of education through the implementation of Kampus Mengajar Angkatan 3 at SDN Segara Makmur 02. The programs implemented were teaching assistance, calistung post, literacy corner, outdoor classes, learning media innovation, assistance in mastering digital literacy, character education, assistance in the implementation of Class AKM, and administrative assistance. Keywords: kampus mengajar, education quality, primary education